2019
DOI: 10.1590/1518-8345.2951.3226
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated to inconsistent condom use among sex workers

Abstract: Objective:to analyze the factors associated to the inconsistent condom use among sex workers.Method:a transversal study, carried out in prostitution area, using the Respondent Drive Sampling. The sample was calculated based on the information by the Sex Workers Association: 600 female sex workers. The study selected seven women with different characteristics regarding color, age, and place of work, who were called seeds. After the participation, they received three coupons to recruit other participants in orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 32 publications
(38 reference statements)
1
9
1
8
Order By: Relevance
“…For younger men in studied countries, the ever-dominant masculinity role orientation in many SSA societies might force them not to consistently wear condoms even for paid sex, despite the associated risk because of their preference for ''flesh to flesh" sex [45]. Similar to previous research [31,[46][47][48][49][50], wealth quintile and level of education showed the highest odds of consistent condom use among men in the richest wealth quintile and those with secondary level of education paying for sex, compared to their counterparts in the middle wealth quintile as well as those with less and/ or no level of education. Wealth is a common marker of economic status, which is also partly explained by one's educational status.…”
Section: Plos Onesupporting
confidence: 69%
“…For younger men in studied countries, the ever-dominant masculinity role orientation in many SSA societies might force them not to consistently wear condoms even for paid sex, despite the associated risk because of their preference for ''flesh to flesh" sex [45]. Similar to previous research [31,[46][47][48][49][50], wealth quintile and level of education showed the highest odds of consistent condom use among men in the richest wealth quintile and those with secondary level of education paying for sex, compared to their counterparts in the middle wealth quintile as well as those with less and/ or no level of education. Wealth is a common marker of economic status, which is also partly explained by one's educational status.…”
Section: Plos Onesupporting
confidence: 69%
“…This finding was similar to a qualitative study in Indonesia suggested that clients refuse to use condoms because most of them cannot enjoy sexual intercourse, as condoms feel slippery and cold (22). This finding was inconsistent with a study in Brazil in 2019, a low education level is the main factor of clients why they refuse to use condom (23). A study in Uganda showed that low sexual control by FSWs increases inconsistent use by regular clients (24).…”
Section: Discussioncontrasting
confidence: 42%
“…Several studies have concluded that inconsistent condom use can contribute to the spread of STIs [5][6][7]. A systematic review and meta-analysis performed among female sex workers (FSW) globally reported 19.1% (95% CI: 1.7 to 36.4) engaged in unprotected vaginal sex and 46.4% (95% CI: 9.1 to 83.6) engaged in unprotected anal sex [8].…”
Section: Introductionmentioning
confidence: 99%